Four novel mutations identification in 17 beta-hydroxysteroid dehydrogenase-3 deficiency and our clinical experience: possible benefits of early treatment - Wang, Yunpeng; Xu, Yu; Zhang, Huijiao; Yin, Danyang; Pan, Yiming; He, Xiwen; Li, Shuaiting; Cheng, Zhi; Zhu, Gaohui; Zhao, Ting; Huang, Huizhe; Zhu, Min (Frontiers in Endocrinology, 2024)
Individuals with 17-beta-hydroxysteroid dehydrogenase type 3 (17β-HSD3) deficiency face a multitude of challenges, primarily concerning genital appearance, potential malignancy risks, and fertility issues. This study reports our findings from an investigation involving five individuals affected by 17β-HSD3 deficiency, ranging in age from pre-adolescence to adolescence. Notably, we identified four previously unreported mutations in these subjects.Our study included a comprehensive evaluation to determine the potential occurrence of testicular tumors. The results of this evaluation conclusively ruled out the presence of testicular tumors among our study subjects. Moreover, four of these individuals successfully underwent gender transition. Furthermore, we observed significant improvements in genital appearance following testosterone treatment, particularly among patients in the younger age groups who received appropriate treatment interventions. These findings underscore the critical importance of early intervention in addressing concerns related to genital appearance, based on our extensive clinical experience and assessments.In summary, our study provides insights into the clinical aspects of 17β-HSD3 deficiency, emphasizing the vital significance of early intervention in addressing genital appearance concerns. This recommendation is supported by our comprehensive clinical assessments and experience.